Community-based provision of direct-acting antiviral therapy for hepatitis C: Study protocol and challenges of a randomized controlled trial - Wade, A.; Doyle, J.; Gane, E.; Stedman, C.; Draper, B.; Iser, D.; Roberts, S.; Kemp, W.; Petrie, D.; Scott, N.; Higgs, Peter; Agius, P.; et al. (BioMed Central, 2018)
Background: To achieve the World Health Organization hepatitis C virus (HCV) elimination targets, it is essential to increase access to treatment. Direct-acting antiviral (DAA) treatment can be provided in primary healthcare services (PHCS), improving accessibility, and, potentially, retention in care. Here, we describe our protocol for assessing the effectiveness of providing DAAs in PHCS, and the impact on the HCV care cascade. In addition, we reflect on the challenges of conducting a model of care study during a period of unprecedented change in HCV care and treatment. Methods: Consenting patients with HCV infection attending 13 PHCS in Australia or New Zealand are randomized to receive DAA treatment at the local tertiary institution (standard care arm), or their PHCS (intervention arm). The primary endpoint is the proportion commenced on DAAs and cured. Treatment providers at the PHCS include: hepatology nurses, primary care practitioners, or, in two sites, a specialist physician. All PHCS offer opioid substitution therapy. Discussion: The Prime Study is the first real-world, randomized, model of care study exploring the impact of community provision of DAA therapy on HCV-treatment uptake and cure. Although the study has faced challenges unique to this period of time characterized by changing treatment and service delivery, the data gained will be of critical importance in shaping health service policy that enables the elimination of HCV.